Amorphous carbon nitride thin films for electrochemical electrode: Effect of molecular structure and substrate materials. (November 2015) - Kikuchi, Yoshiyuki; Chang, Xijiang; Sakakibara, Yasuaki; Inoue, Kumi Y.; Matsue, Tomokazu; Nozawa, Toshihisa; Samukawa, Seiji
Abstract: We report on the effect of molecular structure and substrate material on amorphous carbon nitride (a-CN:H) electrode properties including film adhesion to the substrate and electrochemical properties. Films were prepared by neutral beam enhanced chemical vapor deposition on different substrate materials (p-type Si, Cu, Ti, and Pt) below room temperature. When depositing on Si, doping nitrogen into carbon improved the electrochemical properties despite weak adhesion to the substrate. Nitrogen in a-CN:H formed two different bonding configurations: incorporation into aromatic carbon rings and hydrogen nitride by infrared (IR) spectroscopy. Therefore, delocalization of π bonds by incorporation of nitrogen affected the electrochemical improvement of the a-CN:H electrode. For samples deposited on a different metal substrate, the adhesion to substrate increased as a function of decreasing oxygen concentration on the metal substrate surface; the Pt substrate performed well with no delamination in our evaluation. The electrochemical properties were improved only in the case of deposition on Pt. Moreover, Pt surface modification by hydrogen beam was also effective; consequently, the electrochemical property of the a-CN:H electrode was superior to the graphite electrode with high temperature annealing. The observed increases in IR spectra of aromatic clusters were in line with the electrochemical improvements of a-CN:H.